Database systems : a practical approach to design, implementation, and management. - Connolly, Thomas M.; Begg, Carolyn E. (Boston : Pearson, 2015)
This text includes material on distributed databases, object-oriented databases, data mining, data warehouses, multimedia databases and the Internet and provides a strong foundation in good design practice.
Includes online access code.
Previous edition: 2010.
Includes bibliographical references and index.
Keywords: Database design; Database management; Computers and IT